Modul Perangkat Lunak Monitoring Daya Sel Surya pada Pelacakan Posisi Matahari Harian Menggunakan Delphi - Martha Adelina Sihombing; Ade Agung Harnawan; Tetti Novalina Manik (Jurnal Fisika FLUX, 2017)
Solar cell power monitoring software module in measurement of current and voltage has been made using data acquisition system device. This module is programmed by Delphi and designed according to the necessities for solar cell monitoring. Necessities for monitoring include many data that will be monitored, i.e: current, voltage, power, time and chart. This module will be integrated with hardware so that the data measured by the hardware can be acquired and displayed by the software module. All monitored data are also displayed through Microsoft Excel which then can be saved. Data acquired from the test are i.e: 0,05 A for current1, 0,2 A for current2, 0,027 V for voltage1, 0,15 V for voltage2, 0,001 W for power1, and 0,004 for power2.